Evaluation of pricing strategies used by informal retail traders in Gweru CBD Area - Mhonde, Christopher; Sikomwe, Shingirai; Nyamwanza, Tonderai (Midlands State University, 2014)
During the period 2006 to 2008 the economy of Zimbabwe experienced economic turbulence resulting in many large and small companies closing. The effect was an increase in unemployment levels to levels close to 80%. In an effort to sustain families, and to supplement incomes many people turned to informal sector trading because of the ease of entry into the sector. This research looks at strategies used by the informal trades to wade completion. The results indicate that the majority use cost-based pricing model, it was also noted that the exit levels are high as are the entry level because money was not being accounted for and sometimes used for other unrelated expenses. This is because the majority of the players in the informal sector are engaging in the trade for survival purposes in a constrained economy. We end the discourse by recommending that the sector has potential for growth but training is needed and structures should be put in place.